Cancer Patients' Long-term Experiences of Participating in a Comprehensive Lifestyle Intervention Study While Receiving Chemotherapy. Issue 1 (January 2020) - Mikkelsen, Hilde Elisabeth Timenes; Vassbakk-Brovold, Karianne; Antonsen, Anne Jørstad; Berntsen, Sveinung; Kersten, Christian; Fegran, Liv
Abstract : Background: Lifestyle interventions seem promising with regard to cancer patients' potential for physical and psychological health benefits and as an empowerment tool. Nevertheless, there is a lack of knowledge concerning cancer patients' longer-term experiences of participating in comprehensive lifestyle interventions. Objective: The aim of this study was to explore cancer patients' long-term experiences of participating in a 12-month individualized comprehensive lifestyle intervention study focusing on physical activity, diet, smoking cessation, and stress management while receiving curative or palliative chemotherapy. Methods: A qualitative design with semistructured interviews of 7 curative and 7 palliative cancer patients was conducted 12 months after inclusion in lifestyle intervention. Data were analyzed following a phenomenological-hermeneutic approach. Results: Two main themes emerged: (1) awareness of the importance of a healthy lifestyle during cancer treatment and (2) individual follow-up; it's good to have someone to talk to. Conclusions: Participation in a 12-month comprehensive lifestyle intervention is both feasible and desirable in curative and palliative patients. However, although the curative participants' motivation and perceived ability to adhere to lifestyle recommendations increased during the intervention period, the palliative participants' perceived ability to adhere decreased even though they were overall highly motivated. Implications for Practice: Our findings encourage the future implementation of lifestyle interventions during cancer treatment, even in cancer patients with advanced disease. However, when implementing lifestyle interventions, healthcare professionals must keep the patients' motivation, perceived ability to adhere to lifestyle recommendations, and individual needs in mind.